(untitled) (Health Renaissance, 2017)
Background: Deliberate self-harm (DSH) is a widespread yet often hidden problem in adolescents and young adults though most DSH can be classified as “non-suicidal self-cutting”, some do go on to commit suicide. DSH present in acute settings of hospitals while limited information are found on reasons and methods for DSH in eastern Nepal. This study aimed at exploring the reasons and methods for deliberate self harm among patients presenting in acute setting of BPKIHS. Objective: To study the methods used and reasons for deliberate self harm in the patients presenting in emergency department and psychiatry outpatient clinics of BPKIHS. Method: Mix method (quantitative and qualitative) was used to conduct cross-sectional study using a pretested semi-structured questionnaire among 400 patients presenting in emergency department and out-patient clinic of Psychiatry department. In-depth interview was conducted among 12 respondents. Result: Four fifth of the patients, used poison as the method for DSH followed by hanging among less than a tenth of the patients. Majority (88%) of the patients did not have any planning before committing act of DSH. Interpersonal conflict (48%), financial reasons (20%) and broken love affairs (16%) are common events triggering DSH. Two-third of patients who presented with DSH were impulsive and almost two-fifth of them had depression. Conclusion: DSH was more common among the younger population. Advocacy to regulate the availability of pesticides for agricultural use may be needed to prevent the at risk population for accessing and using it for self harm. More community based studies to further explore the social aspects for the act of DSH and further researches is needed to design interventions to prevent the act of DSH at community level. Health Renaissance 2015;13(2): 92-104